Muslim and Western Theories of Dreams Interpretation: a Comparative Study of Sigmund Freud and Ibn-e-Sirīn - Saeed-Ur-Rehman, Dr. Muhammad (Al-Amīr Research Journal for Islamic Studies, 2024)
The present study shows a scientific comparison between psychoanalytical dream interpretation and Ibn- e- Sirīn (R.A)’s theory of dream interpretation. A sample of 100 subjects (male& female) was taken from Islamabad region comprising 50 subjects belongs to Practicing Muslims and 50 common Muslims. Their recent dreams are recorded and their interpretation was made. It is concluded that: Majority dreams are wish fulfillment rather than anxiety and symbolic. In Ibn- e- Sirīn (R.A) interpretation of wish fulfillment dreams’ ratio is greater than Freudian interpretation. We may say 58 > 47. In Ibn- e- Sirīn(R.A)’s interpretation of anxiety dreams’ ratio is less than Freudian interpretation. We may say 25<37. In Ibn- e- Sirīn (R.A)’s interpretation of symbolic dreams’ ratio is greater than Freudian interpretation. We may say 17>9. There are 69 dreams in which dreams of both categories are common and in 31 dreams are different. Key Words: Dreams, Interpretation, Western Theories Sigmund Freud, Ibn-e-Sirīn